Congenitally corrected transposition of great vessels in fetus. A study case presentation. - Carlos García Guevara; Elsa Fleitas Ruisanchez; Carlos García Morejón; Andrés Savío Benavides; Francisco Rosales Rivero; Yamelic Bernal (ECIMED, 2011)
The congenitally corrected transposition refers to a malformation in which the atrial andventricular chambers present discordant connections, being also discordant the ventricularchambers with the originated from each of them vessels. It is presented a case with aforementioned characteristics, diagnosed by the second quarter of pregnancy, which at momentof birth presented a rhythm disorder. We propose to report the current case, evidencing theimportance of adequate interpretation of four chambers, left ventricle short axis and threevessels echocardiographic views in the prenatal diagnosis of congenital cardiopathies.